“You should care about marriage”: Vietnamese Women's experience of ambivalent sexism in the STEM workplace - Dan-Tam Pham-Nguyen; Matthew McDonald (SSM - Mental Health)
Anecdotal evidence, commentary in the media, and research conducted by intergovernmental organizations in Vietnam indicate that sexism is commonly experienced by women in the Vietnamese workplace. However, few systematic studies to date have been conducted on the prevalence and types of sexism that Vietnamese women experience. This cross-sectional exploratory study seeks to inquire into women's experiences of sexism in the STEM field and its potential associations with mental health outcomes through the lens of ambivalent sexism theory, which categorizes sexism as benevolent and hostile. Vietnamese women employed in STEM (N = 148) completed online questionnaires assessing experiences of ambivalent sexism, perceived stress and perceived sexism, stress symptoms, depression, and anxiety. The results indicate that benevolent sexism is more common than hostile sexism and that younger women are more frequently targeted. Correlation and regression analyses indicate that benevolent and hostile sexism are positively correlated with women's mental health problems. The findings highlight that despite the gains made in workplace gender equality in Vietnam, sexism continues to pose a problem for women's career development in STEM as well as potential health and safety issues. The study concludes with measures that organizations can undertake to tackle the problem and recommendations for future research in Vietnam to build on this exploratory inquiry.